PENGUJIAN TINGKAT PENERIMAAN PRODUK (UJI ORGANOLEPTIK) PADA MARNING GALAKTAGOG - allania hanung; Wahyuningsih Wahyuningsih; Dyah Ayu Kusuma Wardani; Elsa Putri Sholikhah; Maya Arif Safitri (Sekolah Tinggi Ilmu Kesehatan Estu Utomo Boyolali, 2025)
ABSTRACT Exclusive breastfeeding is essential nutrition for infants aged 0-6 months. However, many mothers still feel their breast milk is insufficient to meet their baby's needs. In various cultures, galactagogue foods are one way to increase breast milk production. This research aims to develop marning into a galactagogue snack that is acceptable to the community. This research began with the production of katuk flour (35%), moringa flour (35%), sesame (25%), and ginger (5%), followed by laboratory testing to determine the results of the prognostic test. Organoleptic testing is necessary to assess product acceptance among the community. Panelists were selected from mothers aged 20-40 who were not allergic to any of the ingredients. There were no statistical differences in the five components tested: color, taste, aroma, texture, and overall assessment of the three product variations. This was because the 30 panelists had different taste preferences, meaning these three variations can be further developed to meet community acceptance. Keywords: Exclusive Breastfeeding, Culture, Galactagogue, Marning, Organoleptic test